PENGEMBANGAN MEDIA FINGER MATH METHOD MENJADI PINBALL GAME UNTUK MELATIH KETERAMPILAN BERHITUNG PERKALIAN SISWA SEKOLAH DASAR - Tasia Puspita Sari (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
Each student has a different level of understanding, the teacher does not use enough teaching aids, which makes learning very everyday and monotonous or uninteresting. And the teacher does not use counting methods to help students understand, so students have a heavy memory load, such as remembering. multiplication. So the researchers developed the Jarimatika method into a pinball game to help determine the multiplication questions from 6 to 15 and design the visualization to make it more interesting. This research uses the Research and Development (RnD) methodology and the Analysis Design Development Implementation and Evaluation research model or usually shortened to the ADDIE method. From the results the percentage of data can be increased to 96.67%. According to Arikunto, 2009: 35 in the media eligibility category it is stated that it is very feasible to be a 6 to 15 multiplication pin ball game media. So that research on media development into a Pinball Game media is interpreted as valid. The ease of application helps students to improve the quality of counting. The conclusions are as follows The following: The development of Jarimatika Media in Mathematics subjects, especially in multiplication of 6 to 15 can be categorized as very suitable for use in learning at the Integrated Islamic Elementary School Insan Kamil Cepogo, according to the assessment of the pretest and posttest as well as questionnaires for class 4 user participants,